2017
DOI: 10.1002/psp4.12160
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Pharmacodynamics of Benralizumab in Healthy Volunteers and Patients With Asthma

Abstract: Benralizumab is a humanized, afucosylated, anti‐interleukin‐5 receptor α, immunoglobulin G (IgG) 1 κ monoclonal antibody. We developed a population pharmacokinetic (PK)/pharmacodynamic (PD) model for benralizumab by analyzing PK and blood eosinophil count data from two healthy volunteer studies (N = 48) and four studies in patients with asthma (N = 152). Benralizumab PK was dose‐proportional and adequately described by a two‐compartment model with first‐order elimination from the central compartment and first‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…When benralizumab PK exposure was stratified by weight groups, no clear differences were observed between devices. Consistent with a previous PK modeling study (19), benralizumab PK exposure was greater for volunteers in the lowest weight group compared with those in the other weight groups. Benralizumab was well-tolerated with low prevalence of ADAs, consistent with previous studies (15)(16)(17).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When benralizumab PK exposure was stratified by weight groups, no clear differences were observed between devices. Consistent with a previous PK modeling study (19), benralizumab PK exposure was greater for volunteers in the lowest weight group compared with those in the other weight groups. Benralizumab was well-tolerated with low prevalence of ADAs, consistent with previous studies (15)(16)(17).…”
Section: Discussionsupporting
confidence: 89%
“…AMES was a multicenter, randomized, open-label, parallel group, Phase I study performed at two sites in Berlin, Germany, and London, United Kingdom. The study included a screening period of 28 days; a single treatment period during which volunteers received benralizumab at the study center on Day 1 and returned for follow up on Days 2,4,5,6,8,15,19,and 43; and an end-of-treatment visit on Day 57.…”
Section: Methodsmentioning
confidence: 99%
“…Benralizumab PK data were initially fitted using a two-compartment model with first-order absorption from the subcutaneous dosing site and first-order elimination from the central compartment, based on a previous population PK analysis of data from early phase studies [ 10 ]. The model was parameterized using bioavailability ( F 1 ) fraction, an apparent absorption rate constant ( k a ), systemic CL, central volume of distribution ( V c ), intercompartmental CL ( Q ), and peripheral volume of distribution ( V p ) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacokinetic (PK) and blood eosinophil count data from early stage clinical studies were modeled to facilitate selection of optimal dose levels and dosing schedule of benralizumab for a phase IIb proof-of-concept study for adult patients with severe asthma [ 9 , 10 ]. Subsequently, two dosing regimens of benralizumab 30 mg (every 4 weeks, or every 4 weeks for the first three doses followed by every 8 weeks) were selected for the following phase III trials: SIROCCO [ 11 ] and CALIMA [ 12 ], which evaluated the effect of benralizumab on the rate of annual asthma exacerbation; ZONDA [ 13 ], an oral corticosteroid (OCS) reduction study; and BISE [ 14 ], a pulmonary function study.…”
Section: Introductionmentioning
confidence: 99%
“…Ternant et al quantified the influence of ADA on IFX PK and reported a 2.7-fold increase in clearance and a 34% decrease in elimination half-life in inflammatory bowel disease patients [275]. ADA is a clinically significant covariate for clearance of number of mAbs like golimumab [276,277], ustekinumab [278,279], anti-IL1β mab [280], daclizumab [281], amatuximab [282], atezolizumab [283] and benralizumab [284] (Table 4). For most of the above cited therapeutic mAbs, the patients developed ADA 12 weeks after initiation of therapy, in line with the known somatic hypermutation kinetics of IgGs [269].…”
Section: Anti-drug Antibodiesmentioning
confidence: 99%